PQL: KONVERSI SINTAKS SQL MENJADI SINTAKS PQL - Sitohang, Benhard; Widagdo, Tricya Esterina (Jurnal Informatika, 2007)
The aim of our research presented was to evaluate the semantic coverability of PQL (Public Query Language) as a query language, compared to SQL (Structured Query Language). Our approach in doing the evaluation was to develop conversion rules from SQL to PQL statements, by using relational expressions as the intermediate language. The SQL syntaxes were grouped into four categories, based on the number of relations used in the queries and whether the queries were nested or not. Based on the conversions results, it can be concluded that all of SQL statements that include one or more relations with natural join operations - with or without nested sub queries - can be converted into PQL statements. Abstract in Bahasa Indonesia : Evaluasi cakupan semantik PQL (Public Query Language) sebagai satu query, dibandingkan dengan SQL, merupakan kajian utama pada penelitian tentang konversi yang dijelaskan pada makalah ini. Pendekatan dalam evaluasi tersebut, dilakukan dengan mengembangkan dan uji-coba konversi dari SQL menjadi PQL, dengan menggunakan operator relasi sebagai media konversi. Dari pengembangan konversi ini telah dapat mengelompokkan, bahwa semua sintaks SQL yang didasarkan pada natural join dan melibatkan 1 atau beberapa relasi, dapat dikonversi menjadi sintaks PQL, baik query yang bersarang (nested) maupun tidak bersarang. Kata kunci: Public Query Language (PQL), Structured Query Language (SQL), model relasi, operator relasi.